Identify and Prioritize the Critical Success Factors in Pharmaceutical Supply Chain and Distribution Using the DEMETEL Technique - Ali Abedini; Hamid Reza Irani; Hamid Reza Yazdani (Tehran University of Medical Sciences, 2019)
Background and Aim: In our country because of the security of production and distribution of medicine, Pharmaceutical producers and distributors are known for profitability. The weaknesses in this industry include low productivity in the raw material supply, inefficiency in Pharmaceutical distribution and increasing corporate finance costs. Therefore, the purpose of this research is to identify and prioritize the critical success factors in SCM and distribution of the pharmaceutical industry in the country to provide effective decision making in this field. Materials and Methods: The research consists of two phases of library and surveying. In the first phase, by searching in scientific databases, CSFs in the supply chain and distribution were identified and were categorized in 25 dimensions. Based on the Pareto principle 9 dimensions out of 25 divided dimensions became the pairwise comparison in DEMATEL method to determine the impact and effectiveness. The statistical Society of this research is pharmaceutical producers and distributors in 2018. We have used 13 experts in marketing, SCM, and distribution of pharmaceuticals companies as samples. For data analysis, Excel and MATLAB software were used. Results: Senior management commitments, use of information technology and government intervention were the first three influential factors and processes, service quality and trust were the first three effective factors. Also, the most challenging factor was the senior management commitment and the least interactive factor was government intervention. Conclusion: Managers can not consider all the factors; they should invest in influential and challenging factors.